An Assessment of the Adriatic Cruise Market for 2023: A Comparative Approach - Antonellini, Luca (An Overview on Business, Management and Economics Research Vol. 2, 2023)
Purpose: The primary objective of this study is to assess the market share of cruises in the Adriatic region regarding the total worldwide in 2023. Methodology/Design/Approach: A novel approach has been employed by utilizing two separate databases, one containing information on ships and the other including information on routes. The analysis centers on a particular itinerary comprising one or several ports situated in the Adriatic region. Moreover, the concept of a "unique passenger" is introduced, which pertains to individuals who are seen as a singular entity while embarking on a cruise in the Adriatic, irrespective of the quantity of ports they may visit. This model has facilitated the analysis of the features of ships that visit the Adriatic region, the market shares of different groups/companies (including the utilization of the Herfindahl-Hirschman Index as an analytical approach), and the duration and seasonality of various routes. The research seeks to cover a gap in the numerous studies on cruises that use the number of passenger movements as a reference point. The fact that it is an ex-ante analysis is its most significant limitation. Findings: The market share of cruise passengers in the Adriatic in 2023, relative to the global total, is within the range of 3.6% to 3.8% (varying according to the specific source of comparison employed). Originality of the Research: The proposed model is applied for the first time in the Adriatic region. In order to establish a comparison with the years preceding 2023, two novel mathematical formulas were introduced, which offer qualitative insights.